FRI0056 LUNG COMPROMISE SCREENING IN PATIENTS WITH EARLY RA. A MULTICENTRIC CROSS SECTIONAL STUDY. (2nd June 2020) - Benavidez, F.; Rodriguez, G.; Riopedre, A.; Mata, D.; Benitez, A.; Peon, C.; Viola, M.; Blanco, E. S.; Molina, H.; Garbarino, C.; Secco, A.; Caceres, A.; et al.
Abstract : Background: Rheumatoid arthritis (RA) affects 0.4-1.3% of general population (1). It can affect lungs in different ways, with interstitial lung disease (ILD) as the most severe. Clinically evident ILD has been reported in 10-42% of patients, with a great impact in prognosis (2). Objectives: To i dentify the prevalence of lung involvement in early rheumatoid arthritis patients (ERA) without previous known lung disease and describe the association between high resolution computed tomography (HRCT), lung functional tests (LFT) and clinical findings. Methods: Cross sectional multicentric study. We included ERA patients (1 year or less since diagnose) consecutively. Patients with previous RA related lung disease or biologic/targeted synthetic Dmard treatment were excluded. HRCT, immunological tests (rheumatoid factor, anti-CCP, ANA), LFT and clinical evaluation were performed. Results: We included 74 patients, 63 (85, 1%) woman, mean (SD) of 47 (17, 7) years. Thirty-seven patients (50%) were current or former smokers. Abnormal findings in HRCT were found in 62 patients (88, 6%): ILD in 6 (8, 6%), airway involvement in 40 (70%) and emphysema in 7 (10%). Ten patients (13, 5%) had abnormal auscultation (2 sibilances, 2 roncus, and 6 crackles). Six patients (8, 1%) had digital clubbing. Regarding immunological tests, 54/61 (88, 5%) patients were positive for Anti CCP, and 53/61 (86, 9%) were positive for FR. We compared features of patients with findings related to RA in HRCT (interstitial and/or airway) with those without them. We found no differences in the mean (SD) of DAS-28 [4, 74 (1, 38) vs 4, 32 (1, 39); p= 0, 27]. The prevalence of anti- CCP was not higher in patients with abnormal HRCT [38/44 (86, 3%) vs 16/17 (94, 1%); p=0, 39]. Patients with abnormal HRCT were older [median (IQR) 50, 5 years (44, 5-59, 5) vs 43 years (32-51); p=0, 008) and showed higher VSG values [mean (SD) 39, 09 (24, 03) vs 27, 38 (17, 6); p= 0, 043]. Abnormal physical examination or dyspnea (class 2 mMRC or higher) was significantly associated with HRCT abnormalities [26 (50%) vs 3 (13, 6%); p=0.003) and the presence of ILD on HRCT was significantly associated with crackles on the auscultation [4/68(6, 25%) vs 2/6 (33, 33%); p 0, 023]. Conclusion: This study shows a high prevalence of lung involvement in ERA patients of less 1 year from diagnosis. Also, we showed a significant association between HRCT and physical examination findings. This data highlights the importance of the clinical examination in Rheumatoid Arthritis patients. More studies with bigger samples and longitudinal follow up are needed to confirm and complete our results. References: [1]Rooney BK, Silman AJ. Epidemiology of the rheumatic diseases. Curr Opin Rheumatol [Internet]. 1999 Mar [cited 2016 Jul 19];11(2):91–7. Available from: http://www.ncbi.nlm.nih.gov/pubmed/10319210 . [2]Antin-Ozerkis D, Evans J, Rubinowitz A, Homer RJ, Matthay RA. Pulmonary Manifestations of Rheumatoid Arthritis. Clin Chest Med [Internet]. 2010;31(3):451–78. Available from: http://dx.doi.org/10.1016/j.ccm.2010.04.003 . Disclosure of Interests: None declared